Reminders of past choices bias decisions for reward in humans - Aaron M. Bornstein (Nature Portfolio, 2017)
Previous work has shown that learning models based on running averages of received rewards can account for sequential choices in value based decisions. Here the authors show that such choices can also be influenced by a process of sampling memories for individual past outcomes, and that the sampled memories are episodic in nature.